Relationship of serum hepatitis B Virus DNA levels with Hepcidin, Pentraxin-3, Zonulin, and Copeptin in chronic hepatitis B patients - Burak Ezer; Mehmet Ozdemir (Journal of Infection in Developing Countries)
Introduction: This study aims to investigate the serum levels of hepcidin, pentraxin-3 (PTX-3), Zonulin, and Copeptin biomarkers, which can be detected by the more cost-effective and practical ELISA method compared to the quantitatively determined HBV DNA by molecular methods, and to contribute to studies on biomarkers that will facilitate the antiviral treatment management of chronic Hepatitis B patients.